FRI0557 Thermographic analysis of hands and wrists of rheumatoid arthritis patients. (12th June 2018) - Gatt, A.; Borg, A.; Mercieca, C.; Grech Scalpello, A.; Camilleri, L.; Gatt, C.; Chockalingam, N.; Formosa, C.
Abstract : Background: Thermography has been utilised in a number of studies in rheumatoid arthritis (RA), 1 however there is a paucity of evidence as regards to the possibility of applying this non-invasive technology to the detection of synovitis of the hands and wrists. With normative data having been already published, 2 it is now possible to compare the thermographic characteristics of RA patients without active synovitis to those with a normal thermal distribution in order to determine the baseline characteristics of RA hands and wrists. This would consequently provide a foundation against which further studies investigating RA patients with synovitis can be compared. Objectives: To determine whether rheumatoid arthritis (RA) patients without active synovitis in their hands exhibit different baseline thermographic patterns of the fingers and palms when compared to healthy individuals Methods: Data from 31 RA patients were compared to 51 healthy controls. Inclusion criteria were confirmed absence of synovitis by clinical examination and musculoskeletal ultrasound in rheumatoid patients. Thermographic imaging of the regions of interest (ROIs) were obtained as per established protocols 2 Results: Significant differences were found between the mean temperatures of the palm regions and fingers of the healthy participants when compared to the palm regions and fingers of their RA counterparts (p=0.001), with the latter group exhibiting higher temperatures in all ROIs. No significant differences were found between ROIs of the palms and fingers of both hands in either group. Logistic regression models confirm that both palm and finger temperature increase significantly in RA Conclusions: RA patients without active inflammation of the hands demonstrate a significantly higher mean temperature compared to healthy individuals. These findings provide evidence that baseline thermal data in RA differs significantly from healthy individuals. Thermal imaging may have the potential to become an adjunct assessment method of disease activity in patients with RA. References: [1] Frize M, Adéa C, Payeur P, Di Primio G, Karsh J, Ogungbemile A. Detection of rheumatoid arthritis using infrared imaging. In: Dawant BM, Haynor DR, eds. 2011. [2] Gatt A, Formosa C, Cassar K, et al. Thermographic patterns of the upper and lower limbs: Baseline data. Int J Vasc Med. 2015. Disclosure of Interest: None declared